THE EFFECTIVENESS OF MODULE DIGITAL YOUTH (DY) AS YOUTH EMPOWERMENT THROUGH CRIME AWARENESS: A CASE STUDY OF SOUTH MALAYSIA - Krishnan, Virishna Muthu; Chethiyar, Saralah Devi Mariamdaran (PEOPLE: International Journal of Social Sciences, 2020)
Throughout the world, crime is predominantly devastating among the youth age group, and such is the case in the Malaysian context. Studies have shown that some youth get involved in crime unknowingly especially crimes involving cyberbullying, spousal physical violence, forced intimacy, and verbal abuse simply because of lack of knowledge on what is considered a crime. The issue of crime affects the youth themselves, their families, and the community at large. It is against this background that the study shares the concept of raising awareness on crime amongst youth’s cybercrime, drug abuse, and sexual abuse through the digital youth program. The study was guided by the structural functionalism theory. The research took a quantitative quasi-cross-sectional study design and raised awareness among 100 students between the ages of 18-23 (emerging adults) at College Genius, Klang, Selangor, divided into the experimental group and the control group. The ratings of awareness projects can be assessed before and after using police standardized crime awareness appraisal questionnaire. Results of the study show a significant difference in crime knowledge before and after intervention for the experimental group and no difference significant for the control group after the intervention highlighting the Digital Youth Program to be significant in raising awareness on crime to the youth. The study recommends for future studies to expand the Digital Youth Program to various parts of Malaysia among the youth.